Technology-Enhanced Teaching for English Grammar: Is It Undeniable? - Rumondang Miranda Marsaulina (International Journal of Education, Information Technology, and Others, 2020)
This study compares the results among the use of traditional approach, technology-enhanced teaching and student-centered strategy for directing the first-year Diploma 3 of Informatics Engineering students to improve their fundamental English grammar. The study aims to examine the teaching method which tends to impact best on the students’ grammar knowledge and skills. The participants were 122 first-year Diploma 3 of Informatics Engineering class of 2015, 2016, and 2017. The study was conducted using Mettetal’s Classroom Action Research. The data gathered were quantitative and qualitative. Quantitative data describing the result of each method were based on the students’ final grade on the grammar class. The data were tested by using non-Parametric Kruskall Wallis test and Post Hoc Mann Whitney U test. Qualitative data to analyze the aspects causing the results were derived from the class observations of the teaching team and students’ feedback. The study revealed that students taught in technology-enhanced environment improved their grammar skills and knowledge only slightly better than those taught by traditional approach, and the result of using technology-enhanced teaching was even far below than that of the students taught by student-centered method with only sufficient technology use. Students’ low motivation to do drills at will, the complexity of evaluation tests, and the lecturer’s fair pedagogy skills were the reasons behind the unsatisfactory outcomes of technology-enhanced teaching. The study contributes to show a lecturer’s pedagogic skill especially for motivating students in cognitive learning engagement matters more than technology dependence in English grammar class.